Computational fluid dynamics modelling of solid suspension in stirred tanks - Sardeshpande, Madhavi V.; Ranade, Vivek V. (Current Science, 2012)
Solid suspension and mixing are crucial in many important processes, including multiphase catalytic reactions, crystallization, precipitation, etc. In recent years, various efforts have been made to numerically simulate solid-liquid flows in stirred vessels using computational fluid dynamics (CFD). In this article, we present a brief account of our group's efforts at developing and using CFD models for simulating solid suspension in stirred tanks. Computational models were developed and evaluated by comparing model predictions with our data as well as published experimental data. A variety of experimental techniques ranging from torque and wall pressure fluctuations to ultrasound velocity profiler were used. Efforts were made to develop appropriate sub-models for capturing influence of the prevailing turbulence and solid volume fraction on effective inter-phase coupling terms. A hysteresis in variation of the height of the cloud of suspended solid with impeller rotational speed was observed. The hysteresis, besides having applications in realizing better suspension at lower effective power consumption, also offers an attractive evaluation test for CFD models. A new way to carry out dynamic settling of solid cloud by sudden impeller stoppage has been developed. The approach, models and results presented here will be useful for extending applications of CFD models for simulating industrial stirred slurry reactors as well as further research in the field.
Keywords: computational fluid dynamics; hysteresis; solid suspension; stirred tanks